Improving linkage of data on looked after children in Scotland through operational innovations - Robson, Siân; Seaman, Rosie (International Journal of Population Data Science, 2025)
Objectives This project is scoping ways to improve the linkage rate of the Scottish Government’s longitudinal Looked After Children (LAC) dataset to other datasets by providing an appropriate, secure and practical mechanism for transferring more identifiers to National Records of Scotland (NRS) - the trusted third-party indexing service in Scotland. Method Local authorities report LAC data annually to the Scottish Government. A pseudonymised longitudinal LAC dataset has been created and ingested to the Scottish National Safe Haven for research use. The dataset is frequently requested, but data for children who are not in school cannot be linked to other datasets because there is insufficient person identifiable information (PII) to match them to the population spine. Outcomes for a key cohort of vulnerable children are therefore poorly understood. This project is investigating possible innovations to share PII with the NRS indexing service to maximise linkage. Results Options under consideration include Data Processing Agreements between each local authority and NRS; amendment of the existing data transfer from local authorities to Scottish Government to include more PII; and potentially different approaches for historic vs. ongoing data. The Information Governance and operational processes around each option are being considered. Local authorities will be consulted on which method would be agreeable. Public engagement will be conducted to seek Looked After Children’s views on the proposed process. Relevant strategic and operational groups will be asked for support to encourage buy-in across local authorities. Conclusion This project will suggest a process to improve prospects for linkage of data on different aspects of Looked After Children’s lives and therefore enable a more holistic, longitudinal perspective, leading to better-informed decisions about policy and practice.